Teaching applied politics: From employability to political imaginary. (February 2018) - Bacon, Edwin
The growth of applied politics teaching in recent years is often conflated by academics, institutions, and professional associations with the employability agenda increasingly promoted by government. Many academics – politics faculty to the fore – object to the imposition of neo-liberal values on universities, the commodification of higher education, and a focus on employability in their teaching. These developments, coupled with a sense that the teaching of practical politics lacks intellectual rigour, undermine the growth of applied politics courses and programmes. There is, however, no reason why applied politics teaching must embrace neo-liberal norms. Nor is the alternative the introduction, as has happened in a few institutions, of courses teaching the practice of radical activism. Norms and values in applied politics can come from students, producing content and knowledge as they develop skills and approaches to practical politics. Applied politics itself represents a bridge between political science and political life beyond the university and serves the needs of students across the 'careerist-activist' spectrum. Far from being intellectually light, a values-focused approach to applied politics has a pedagogical depth beyond that offered in much of the current politics curriculum. It offers a pedagogy not just of information but of formation and transformation.